The complexities and challenges of sexual dysfunctions diagnosis in females: A case report - Farnaz Farnam (Zanjan University of Medical Sciences and Health Services, 2019)
Background: Managing sexual problems requires skill and enough time and precision. The patient's chief complaint and data can alter through treatment processes. Objectives: This case report is about the complexities and challenges of sexual dysfunctions diagnosis in females. Methods: The present study reports different diagnoses of a woman referred to a sexual clinic. Results: A 24 years old woman with a history of 4-year unconsummated marriage due to primary vaginismus referred to a sexologist. Previous visits by gynecologists, psychiatrists, and urologists showed no mental or medical problems in the couple. The woman reported that marriage had been done with the couple's consent, she loved her husbands, and no conflict existed between the couple. After examining history and assessing sexual distress and function by means of FSDS-R and BISF questionnaires, routine treatment of vaginismus such as desensitization was initiated through vaginismus diagnosis. Some sessions later, woman's narratives and examinations led to the diagnosis of sexual aversion (sexual aversion was one of the DSM-IV categories). Next interviews with the couple revealed that the woman did not suffer from any sexual dysfunction. The woman replaced her husband with her dead father and consequently was not able to have any sexual relationship with her, although she loved him. Conclusion: In the mentioned case, 11 visits and more than 10 hours' interview were done. One session with the husband alone, three sessions with the couple, and seven sessions with the wife were held. Three distinctive diagnoses were considered. Although enough time was devoted to introduction in the first session (60 minutes), correct diagnosis needed more visits. The process of the client's trust to the therapist occurred gradually, and frequent interviews and separated man and woman visits were crucial for precise diagnosis